Inflation Persistence and Implications for the Euro Area - MIRDALA, Rajmund (Theoretical and Practical Research in Economic Fields, 2023)
The deceleration of consolidation trends subsequent to the previous financial crisis has had a mitigating effect on price dynamics. Furthermore, the expansionary fiscal and monetary measures implemented to stimulate the recuperation of crisis-affected economies did not yield substantial inflationary consequences. The disruptions in supply chains caused by the pandemic, the increased use of expansionary fiscal and monetary policies in response to the outbreak, and the influence of geopolitical factors such as energy prices have recently rekindled the capacity of price level dynamics to react. When the underlying economic factors deteriorate, it leads to an increase in vulnerability and a decrease in the ability of the euro area to withstand adverse events. During periods of economic prosperity, the monetary policy implemented by the European Central Bank (ECB) has the tendency to enhance the convergence of countries within the euro area and bolster its resilience against adverse economic disturbances. The findings of the article provide support for arguments emphasizing the need to adjust the institutional framework of the euro area, hence reinforcing the rationale for the concept of a two-speed euro area.